Work-Life Balance: The Key to Employee Engagement and Employee Performance - Jordan David; Bobi Adimasta; Eisha Lataruva (LifeSciFi, 2025)
In the digital era, where work demands are increasingly dynamic and the boundaries between professional and personal life are becoming blurred, Work-Life Balance (WLB) has emerged as a central issue in human resource management. This study aims to analyze the influence of WLB on employee engagement and employee performance through a systematic literature review using the Job Demands-Resources (JD-R) Theory. Data were collected from 24 Scopus-indexed scientific articles (Q1–Q3) published between 2023 and 2025. The findings indicate that WLB plays a crucial role as a mediator between organizational support and employee engagement, and directly contributes to improving employee performance, as measured by quality, timeliness, and supervisor satisfaction. These results highlight that effective WLB policies not only enhance employee well-being but also support overall organizational productivity and success. The practical implications of this research emphasize the importance of flexible work arrangements, organizational support, and the wise use of technology to create a healthy and sustainable work environment.